PENGARUH FASILITAS TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA CAFE SKY GARDEN WONOBOYO DI BONDOWOSO - Hidayat, Rasiful; Arief, Mohammad Yahya; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2022)
The purpose of the study was to determine the effect of facilities on consumer satisfaction through purchasing decisions as an intervening variable at the Sky Garden Cafe Wonoboyo in Bondowoso. The sampling technique used in this study is probability sampling with a simple random sampling technique with the Slovin formula with a tolerable error rate of 10% as many as 98 people. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that the facilities have a positive and significant effect on purchasing decisions, facilities have a positive and significant effect on consumer satisfaction, purchase decisions have a positive and significant effect on consumer satisfaction, facilities have a positive but not significant effect on consumer satisfaction through purchase decision